Virtual Planning and 3D Printing in Contemporary Orthognathic Surgery - Roy, Tulsi; Steinbacher, Derek M. (Seminars in Plastic Surgery, 2022)
Orthognathic surgery is a powerful tool to improve facial balance, form, and function. Virtual planning and three-dimensional printing has improved our ability to visualize complex anatomy, consider various iterations and execute complex movements, and create accurate splints, plates, and cutting guides. This article will outline the distinct advantages of the use of virtual surgical planning over traditional planning, and it will explore the utility of computer-aided design and technology within contemporary orthognathic surgery, including its expanded applications and limitations.
Keywords: orthognathic surgery; virtual surgical planning; CAD/CAM